Healthy lifestyles and chronic disease prevention and control - Chun LI; Limin WANG (Zhongguo gonggong weisheng)
With the rapid development of China′s economy and the swift changes in social life, chronic diseases have become a major threat to residents′ health, placing a heavy burden on individuals, families, and society. Unhealthy lifestyles such as smoking, excessive alcohol consumption, unhealthy diets, insufficient physical activity, lack of weight management, and inadequate sleep are important risk factors for chronic diseases and are closely related to the occurrence of cardiovascular and cerebrovascular diseases, cancer, chronic respiratory diseases, and diabetes. Adhering to a healthy lifestyle and changing unhealthy behaviors are the most effective and cost-effective strategies for preventing and controlling chronic diseases. However, the prevalence of healthy lifestyles among the population remains low, necessitating support from the social environment and policy levels. A comprehensive approach using multiple methods is needed to create a favorable social atmosphere conducive to the development of healthy lifestyles, thereby achieving the long-term goals of chronic disease prevention and control.